Do you see what I see? A social capital perspective on microtask gig worker opportunity recognition within electronic networks of practice. (April 2023) - Di Gangi, Paul M.; Howard, Jack L.; Goh, Samuel H.; Thatcher, Jason Bennett
Abstract: Microtask gig workers (MGWs) rely on digital platforms to arrange work agreements with requesters to complete well-defined microtasks. Many MGWs use an electronic network of practice (ENP) to facilitate information sharing about desirable and undesirable microtasks. This study uses social capital theory to theorize how social capital's dimensions – structural, cognitive, and relational – shape the development of uncertainty-reducing and individualized-skill benefits. Based on survey data from 436 Amazon Mechanical Turk (MTurk) workers, the findings demonstrate that unique social capital dimensions affect specific ENP benefits. Understanding the communication style of an ENP (i.e., cognitive social capital) positively influences the uncertainty-reducing benefits of microtask information quality (MIQ) related to MTurk work. Combined with expectations of reciprocity and trust in ENP members (i.e., relational social capital), MIQ shapes microtask opportunity recognition (MOR), whereby individual MGWs identify opportunities to complete financially beneficial microtasks. The present study demonstrates that contextual factors, based on the coopetive nature of microtask ENPs, affect the interrelated structure of social capital theory and its underlying dimensions. Lastly, post hoc findings demonstrate the influence of MOR on MGWs' financial performance, challenging previously held assumptions about the role of MIQ within the microtask literature. Highlights: This study uses social capital theory (SCT) to examine the benefits of electronic networks of practice for gig workers. This study proposes a link between SCT and individualized-skill benefits for microtask gig workers. Cognitive social capital positively influences relational social capital and microtask information quality (MIQ). Relational social capital and MIQ positively shape microtask opportunity recognition (MOR). Post-hoc analysis shows that MOR directly impacts monthly earnings, while MIQ does not.